1989
DOI: 10.1021/ic00314a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of titanium/cobalt complexes with Ti-O-C-Co bridges

Abstract: Reactions between titanium metallocene dicarbonyls and dicobalt octacarbonyl were investigated and found to give a variety of Ti/Co complexes depending on the reaction conditions. Reaction between CpzTi(CO)z and C O~( C O )~ in nondonor solvents led to the formation of the known CpzTi[OCCo3(CO)9]z via a novel redox/cluster-building process. However, reaction between CP,T~(CO)~ and CO,(CO)~ in tetrahydrofuran led to the formation of the ionic compound [CP~T~(THF)~] [Co(CO),]. A mechanism in which isocarbonyl br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…c The blue bis(cyclopentadienyl)bis(tetrahydrofuran)titanium(III) tetraphenylborate salt was isolated and identified by an X-ray crystal structure analysis. The molecular structure of the Cp 2 Ti(THF) 2 + cation in the crystal structure of 7 is analogous to the structures recently observed for several closely related examples ([Cp 2 Ti(THF)(acetonitrile) + ]BPh 4 - ,9a [Cp 2 Ti(THF) 2 + ]Co(CO) 4 - ,9b and [Cp 2 Ti(pyridine) 2 + ]BPh 4 - 9c ). In 7 , the (THF−oxygen)−Ti−(THF−oxygen) angle is 77.49(7)°; the corresponding Ti−O distances are 2.208(2) and 2.239(2) Å (further details about the structure of 7 are provided with the Supporting Information).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…c The blue bis(cyclopentadienyl)bis(tetrahydrofuran)titanium(III) tetraphenylborate salt was isolated and identified by an X-ray crystal structure analysis. The molecular structure of the Cp 2 Ti(THF) 2 + cation in the crystal structure of 7 is analogous to the structures recently observed for several closely related examples ([Cp 2 Ti(THF)(acetonitrile) + ]BPh 4 - ,9a [Cp 2 Ti(THF) 2 + ]Co(CO) 4 - ,9b and [Cp 2 Ti(pyridine) 2 + ]BPh 4 - 9c ). In 7 , the (THF−oxygen)−Ti−(THF−oxygen) angle is 77.49(7)°; the corresponding Ti−O distances are 2.208(2) and 2.239(2) Å (further details about the structure of 7 are provided with the Supporting Information).…”
Section: Resultssupporting
confidence: 81%
“…In contrast, the (σ-propynyl)(tetrahydrofuran)TiCp 2 + cation is decomposed in ca. 3 days at ambient temperature to yield the known paramagnetic titanium(III) complex [Cp 2 Ti(THF) 2 + ]BPh 4 - ( 7 ) 9a…”
Section: Resultsmentioning
confidence: 99%
“…As described above, the Ti atom in all of the reported Ti−Co 3 complexes is linked to the Co 3 moiety by an isocarbonyl bridge. In contrast, it is known that there are two types of Ti−Co heterobimetallic complexes: one is the type that has a Ti−OC−Co isocarbonyl bridge, ,,, whereas the other is the type that bears a Ti−Co direct bond . As shown in Figure , the molecular structure of 5 revealed that 5 is a heterobimetallic complex whose two metals are linked by an isocarbonyl bridge, Ti−OC−Co.…”
Section: Resultsmentioning
confidence: 99%
“…A survey conducted of the Cambridge Structural Database for such compounds revealed [Cp 2 Ti(THF) 2 ] + [Co(CO) 4 ] 2 , 7, an easily synthesized complex. 56 This compound was active for epoxide carbonylation, though less robust and efficient than 1. However, 7 proved to be a very active catalyst for aziridine carbonylation, producing several b-lactams in good or excellent yield.…”
Section: [Lewis Acid] + [Co(co) 4 ] 2 Catalystsmentioning
confidence: 98%
“…The well-defined nature of catalyst 1 has permitted us to design a number of related catalysts for epoxide-expansion carbonylation (Scheme 13). [49][50][51][52][53][54][55] We have also found that the 56 7, is an active catalyst for this reaction, though it finds greater utility in aziridine carbonylation (see section 6.2). 57 Each of these catalysts features a metal cation to which two THF ligands are bound in the solid state, substantiating its Lewis acidity.…”
Section: Development Of the Catalytic Reactionmentioning
confidence: 99%